Haemodynamic Consequences in Immediate Postoperative Period in Comparison between Open and Laparoscopic Cholecystectomy” - Banu, Mst Sabiha; Mondol, Mohammmad Shaddam Hoshain; Das, Rajat Shuvra; Ali, Md Arman; Shathi, Ishrat Jhahan; Khatun, Mst Habiba; Rahman, Kazi Monisur (Journal of Dhaka Medical College, 2021)
Background: Laparoscopic cholecystectomy has emerged as a popular alternative to traditional open cholecystectomy in the management of cholelithiasis. It has several advantages .Pneumoperitoneum and trendelenburg positioning causes release of stress hormones and ultimately changes in hemodynamic parameters. Stretching of peritoneum, abdominal wall associated with postoperative pain. So maintenance of haemodynamic stability, immediate postoperative pain control continues to be a major challenge for the anaesthesiologists. Methods: Sample was selected by non-probability sampling technique in two groups distributed as- Group-L (Laparoscopic cholecystectomy, n=30) and Group-O (opencholecystectomy, n=30). Detailed history taking, physical examination and routine lab investigations were done. Approval of the study was obtained by the local Ethical Committee. Post-operative complications, postoperative pain, frequency and pattern of cardiovascular complications, frequency and pattern of respiratory complications were evaluated and compared between thegroups Result: In both groups female were predominant. In this study haemodynamic status (Heart rate, SBP, DBP, MBP) in different phases of anaesthesia, surgery and postoperative follow-up (at 4th hour, 8th hour, and 12th hour) has been observed. Conclusion: This study confirms the feasibility and safety of laparoscopic cholecystectomy is better than open technique in terms of attenuation of better haemodynamic stability, better postoperative pain control and less requirement of analgesia. J Dhaka Medical College, Vol. 28, No.2, October, 2019, Page 184-189